2014
DOI: 10.1111/jphp.12192
|View full text |Cite
|
Sign up to set email alerts
|

Oral calcium pectinate-insulin nanoparticles: influences of alginate, sodium chloride and Tween 80 on their blood glucose lowering performance

Abstract: Physicochemical responses of additives in vivo affected blood glucose regulation property of pectin-insulin nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In vitro drug release study showed undetectable levels of insulin release from the AN even after 6 h of incubation in the dissolution medium. The alginate has a p K a value of 3.65, while the amphoteric insulin molecule has an isoelectric point of 5.3 . The nanoparticles were prepared by mixing the negatively charged alginate (dissolved in NaOH) with the positively charged insulin (dissolved in HCl).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro drug release study showed undetectable levels of insulin release from the AN even after 6 h of incubation in the dissolution medium. The alginate has a p K a value of 3.65, while the amphoteric insulin molecule has an isoelectric point of 5.3 . The nanoparticles were prepared by mixing the negatively charged alginate (dissolved in NaOH) with the positively charged insulin (dissolved in HCl).…”
Section: Resultsmentioning
confidence: 99%
“…The alginate has a pK a value of 3.65, 47 while the amphoteric insulin molecule has an isoelectric point of 5.3. 48 The nanoparticles were prepared by mixing the negatively charged alginate (dissolved in NaOH) with the positively charged insulin (dissolved in HCl). Complex formation with the alginate would prevent the insulin from being released from the formed matrix.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These are prepared from natural or synthetic polymers. Natural polymers studied for preparation and evaluation of oral insulin nanoparticles include chitosan (Lin et al, 2007b;Sadeghi et al, 2008;Rekha and Sharma, 2009;Yin et al, 2009;Avadi et al, 2010;Su et al, 2012;Fonte et al, 2012;Chuang et al, 2013;Li et al, 2013b;Mansourpour et al, 2015), alginate (Kadir et al, 2013;Wong and Sumiran, 2014), gelatin, albumin (Rieux et al, 2006;Woitiski et al, 2011) and lectin (Ghilzai, 2003). Synthetic polymers used for nanoparticle formulation include acrylates and its derivatives (Sajeesh and Sharma, 2006;Damge et al, 2010;Perera et al, 2009;Socha et al, 2009), polylactic-co-glycolic acid derivatives (Carino et al, 2000;Shi et al, 2008;Han et al, 2009;Zhu et al, 2015).…”
Section: Nanoparticles Developed For Oral Delivery Of Insulinmentioning
confidence: 99%
“…[23][24][25] Calcium pectinate-insulin NPs formed from a mixture of pectin-insulin at pH 3 were associated with a release of 12.6% ± 3.2% and 21.7% ± 8.7% insulin at 8 and 24 h of dissolution in simulated intestinal medium due to the sustained-release characteristics effect of pectin-insulin interaction. 26 Oral administration of zinc oxide NPs [ Figure 1] also resulted in signifi cant antidiabetic effects -with improved glucose tolerance, higher serum insulin (70%), reduced blood glucose (29%), reduced non-esterifi ed fatty acids (40%) and reduced triglycerides (48%). 27 Insulin should be enveloped in a matrix-like system to protect it from gastric enzymes.…”
Section: Oral Insulinmentioning
confidence: 99%